Rediscovery of Hopea canarensis Hole (Dipterocarpaceae) - an Endemic and Little Known Species from the Western Ghats of Karnataka, India - Ravikumar, K.; Goraya, G. S. (Indian Forester, 1999)
Hopea canarensis Hole has been rediscovered from the type locality after a lapse of nearly 80 years and is described here in detail with notes on phenology, distribution and associated plants. The differences between Hopea canarensis and two closely allied Hopea species are tabulated.